Tuning complexation of carboxymethyl cellulose/ cationic chitosan to stabilize Pickering emulsion for curcumin encapsulation. (January 2021) - Zhu, Xiangwei; Chen, Jianjun; Hu, Yuxi; Zhang, Ni; Fu, Yuqing; Chen, Xiaoqiang
Abstract: Carboxymethyl cellulose (CMC) is an economical and easily available cellulose derivative that ionizes in water and is used in several charge-related interfacial applications. However, compared with other chemically functionalized cellulose derivatives, such as cellulose nanocrystals, the development of CMC-based (CMC as the major ingredient) O/W emulsions remains unexplored. In this study, we synthesized a CMC and quaternized chitosan (QCS) complex for the preparation of Pickering emulsions. Partially protonated CMC was complexed with QCS, followed by neutralization at pH 7 to obtain the CMC/QCS (CQ) particles. The prepared CQ-stabilized emulsion showed a gel-like rheological behavior and exhibited emulsion stability against several environmental stresses, including pH, salt, temperature, and long-term storage. The curcumin was then encapsulated in the CQ-stabilized emulsion and displayed a reduced degradation rate. This study provides a new route for the development of a Pickering emulsion delivery system with improved stability, sustainability and reduced complexity. Graphical abstract: Image 1 Highlights: Complexation was induced between carboxymethyl cellulose and cationic chitosan. The complex particle was an eligible candidate to prepare O/W emulsion. The Pickering emulsions were stable against pH, salt, temperature and long-term storage. Curcumin was encapsulated in the emulsion and exhibited increased stability.